Cytochrome b5 reductase deficiency and hereditary methemoglobinemia - Prchal, Josef (Henry Stewart Talks, 2007)
Formation of methemoglobinemia, Review of methemoglobinemias types, Cytochrome b5 reductase (Cytb5 R), Mutations and clinical phenotypes of Cytb5 R deficiency, Differential diagnosis from other methemoglobinemias, Therapy of methemoglobinemia
Archived at 2018/02/27